The Relationship between the Level of Compliance of Taking Hypertension Medication and the Blood Pressure of Prolanis Patients in the Working Area of the Tilango Health Center - Annisa Baili; Nasrun Pakaya; Sitti Fatimah M. Arsad (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Hypertension is one of the chronic diseases that requires long-term management because it can cause complications if not controlled. One of the important factors in blood pressure control is the patient's adherence to taking antihypertensive drugs regularly. Patients who are members of the Chronic Disease Management Program (Prolanis) are expected to have better blood pressure control through routine health monitoring and continuous education. This study aims to determine the relationship between the level of compliance with hypertension medication and the blood pressure of Prolanis patients in the Working Area of the Tilango Health Center, Gorontalo Regency. This study is a quantitative research using a correlational analytical design with a cross sectional approach, involving 53 respondents who were taken using purposive sampling techniques. The results showed that the majority of respondents had medication adherence in the moderate category as many as 29 people (54.7%), while the majority of respondents' blood pressure was in the mild category as many as 27 people (50.9%). Based on the results of the Chi-Square test, a p value of < 0.05 was obtained, so it can be concluded that there is a significant relationship between the level of compliance with taking hypertension medication and the blood pressure of Prolanis patients in the Tilango Health Center Working Area, Gorontalo Regency, where the better the patient's level of adherence in taking medication, the more controlled the patient's blood pressure.